2019
DOI: 10.3329/bjsir.v54i4.44570
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal concentration and health risk assessment in commonly sold vegetables in Dhaka city market

Abstract: This study assesses the levels of heavy metals in vegetables (Cucumis sativus, Solanum lycopersicum, Ipomoea aquatica, Amaranthus cruentus, Basella alba, Brassica oleracea, Musa acuminata) collected from Kawran Bazar vegetable market located in Dhaka, Bangladesh. Also, it examines potential health risks from the consumption of these vegetables. The samples were randomly collected, processed and analyzed for heavy metals using Atomic Absorption Spectrophotometer. Among the vegetables Basella alba had the highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
1
3
0
2
Order By: Relevance
“…The authors showed that the application of mining effluents as organic amendments was the main cause of soil contamination in market gardens. Furthermore, the studies by [12][13][14] showed that the vegetables produced in the market gardens and sold in Lubumbashi markets presented high levels of trace metal elements (TMEs) above the WHO toxicity threshold. Southeast of Casablanca (Morocco), crop irrigation with industrial effluents containing high loads of heavy metals was found to contaminate five vegetable crops with As, Cd, Cr and Cu [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The authors showed that the application of mining effluents as organic amendments was the main cause of soil contamination in market gardens. Furthermore, the studies by [12][13][14] showed that the vegetables produced in the market gardens and sold in Lubumbashi markets presented high levels of trace metal elements (TMEs) above the WHO toxicity threshold. Southeast of Casablanca (Morocco), crop irrigation with industrial effluents containing high loads of heavy metals was found to contaminate five vegetable crops with As, Cd, Cr and Cu [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the TTHQ was not >1, and it was concluded that all the studied fruits and vegetable were safe to consume. However, a previous study reported the heavy metal status and presence of arsenic in a rural area in Bangladesh [25], and the levels of trace metals have also been mentioned in the vegetables growing near a mining area in Andhra Pradesh (India, southeast Nigeria) [26][27][28]. Figure 6 depicts the health risk index of iron, manganese, and zinc with HI < 1.…”
Section: Resultsmentioning
confidence: 98%
“…Water spinach had the highest Mn content (207 mg/kg), followed by green amaranth (113 mg/kg). The high ability of leafy vegetables to absorb metals is possibly due to the leaves being the primary component of photosynthesis, where metals are carried to the leaves by mass flow during strong transpiration [8]. Besides that, water spinach and green amaranth are both dwarfish plants with leaves that are closer to the ground, easily exposing the foliage to contaminated soil.…”
Section: Resultsmentioning
confidence: 99%